Integrated Marketing Communication Mix Elements and Adoption of a Sports Culture: The Case of Academic Staff of Chartered Public Universities in Nairobi City County, Kenya - Mulili, Benjamin Mwanzia; Maina, Samuel Mwangi; Kinyuru, Reuben Njuguna (European Scientific Journal, ESJ, 2025)
Adoption of a sports culture occurs when people make sports be part of their lives. This study investigated the mediating role of lifestyle habits and the moderating role of socio-ecological factors in the relationship between the integrated marketing communication mix elements and adoption of a sports culture among academic staff of chartered public universities in Nairobi City County, Kenya. The inquiry was based on the theory of planned behaviour (TPB), communication theory, Attention-Interest-Desire-Action (AIDA) model, and the diffusion of innovation theory. The realism paradigm and a descriptive survey research design were used for the study. The researchers sampled 372 academic staff members from five chartered public universities based in Nairobi City County using stratified random sampling. Binomial logistic regression was used in the data analysis since the dependent variable was categorical in nature. The study established that integrated marketing communication mix elements predicted the adoption of a sports culture, with lifestyle habits mediating and socio-ecological factors moderating the relationship between integrated marketing communication mix elements and adoption of a sports culture by the academic staff members of the identified institutions. The study recommends that managers of health-promoting sports clubs should consider the integrated marketing communication mix elements, lifestyle habits, and the socio-ecological factors when designing their communication programs.